2017
DOI: 10.1159/000484480
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Genistein Supplementation on Vitamin D Levels and Bone Turnover Markers during the Summer in Healthy Postmenopausal Women: Role of Genotypes of Isoflavone Metabolism

Abstract: Aims: The objective of this study was to determine whether vitamin D and genistein supplementation had an additive beneficial effect on levels of vitamin D and bone markers and whether this effect was mediated by genes regulating isoflavone metabolism. Materials and Methods: We carried out a prospective study in postmenopausal women randomized to calcium and vitamin D supplementation or calcium, vitamin D, and genistein supplementation. Vitamin D, parathyroid hormone (PTH), cross-linked C-telopeptide (CTX), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Lastly, administration of isoflavones or genistein alone for 1 to 24 months did not alter PTH in postmenopausal women [ 78 , 92 , 180 , 181 , 182 , 183 ]. Only a cross-sectional study carried out with Chinese women found that postmenopausal women with a high intake of isoflavone had lower serum PTH levels [ 184 ].…”
Section: Effect Of Phytoestrogen Intake On Hormones Related To Bonmentioning
confidence: 99%
“…Lastly, administration of isoflavones or genistein alone for 1 to 24 months did not alter PTH in postmenopausal women [ 78 , 92 , 180 , 181 , 182 , 183 ]. Only a cross-sectional study carried out with Chinese women found that postmenopausal women with a high intake of isoflavone had lower serum PTH levels [ 184 ].…”
Section: Effect Of Phytoestrogen Intake On Hormones Related To Bonmentioning
confidence: 99%
“…Genistein, a phytoestrogen, is one of the main isoflavones in soy and it modulates ER signalling by a genomic effect. [15][16][17] Taking into account the above and focusing on the effect of the estrogens on the lipid profile, the primary outcome of our study was to determine whether calcium, vitamin D and genistein supplementation had a beneficial additive effect on serum lipid profile. The secondary outcome was to determine whether this effect was mediated by polymorphisms in ER genes.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens are plant‐derived compounds that have structural similarity to estrogen and that are able to bind to the ERs. Genistein, a phytoestrogen, is one of the main isoflavones in soy and it modulates ER signalling by a genomic effect …”
Section: Introductionmentioning
confidence: 99%
“…Another study suggests that phytoestrogens like genistein could decrease bone turnover, preventing osteoporosis [276]. However, other clinical trials did not find significant results in improving bone density [277][278][279], so there is a controversy about this ability.…”
Section: Endometrial Cancermentioning
confidence: 99%